Extended beyond the Bodies - Katrin Alekand (Journal of Ethnology and Folkloristics)
Review of the publication A Companion to the Anthropology of the Body and Embodiment, edited by Frances E. Mascia-Lees. Blackwell Companions to Anthropology, Vol. 19. Wiley-Blackwell, 2011. xxv+529 pages.